Supercomputer Modeling of Hydrochemical Condition of Shallow Waters in Summer Taking into Account the Influence of the Environment - Sukhinov, Alexander I.; Chistyakov, Alexander E.; Nikitina, Alla V.; Belova, Yulia V.; Sumbaev, Vladimir V.; Semenyakina, Alena A. (Parallel Computational Technologies, 2018)
The paper deals with the development and research of a mathematical model for hydrophysical processes which involves the use of modern information technologies and computational methods with the aim to improve the accuracy of predictive modeling of ecological condition of shallow waters during the summer. The model takes into account the following factors: movement of water flows; microturbulent diffusion; gravitational settling of pollutants; nonlinear interaction of plankton populations; nutrient, temperature and oxygen regimes; and impact of salinity. A scheme with weights is proposed for the discretization of the proposed model. This scheme significantly reduces both error and computation time. The practical significance of the paper is determined by the software implementation of the model and the determination of the limits and prospects of its practical use. Experimental software is designed on the basis of a supercomputer for mathematical modeling of possible development scenarios of shallow water ecosystems taking into account the influence of the environment. For this, we consider as an example the Sea of Azov in the summer period. The software parallel implementation involves decomposition methods for computationally intensive diffusion-convection problems taking account of the architecture and parameters of a multiprocessor computer system. The software complex contains a model for fluid dynamics which includes equations of motion in three coordinate directions.